2020
DOI: 10.1093/jscr/rjaa245
|View full text |Cite
|
Sign up to set email alerts
|

SARS–CoV-2 isolation from an appendix

Abstract: Efforts to recognize SARS–CoV-2 infection have focused on respiratory symptoms such as cough and shortness of breath. Although it is also well known that SARS–CoV-2 infection can cause gastrointestinal symptoms such as abdominal pain, nausea, vomiting and diarrhoea, there are emerging reports of SARS–CoV-2 infection causing surgical pathology. We present the first case report of SARS–CoV-2 infection directly causing acute appendicitis, first suspected due to highly atypical histological features and later conf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…Portincasa et al suggest an unconfirmed hypothesis that the virus could translocate from the gut lumen into the liver via portal flow, negatively affecting hepatic cells [ 7 ]. SARS-CoV-2 could also reach the appendix via oropharyngeal contamination or appendicolith, resulting in bacterial translocation and appendicitis [ 8 ].…”
Section: Main Textmentioning
confidence: 99%
See 2 more Smart Citations
“…Portincasa et al suggest an unconfirmed hypothesis that the virus could translocate from the gut lumen into the liver via portal flow, negatively affecting hepatic cells [ 7 ]. SARS-CoV-2 could also reach the appendix via oropharyngeal contamination or appendicolith, resulting in bacterial translocation and appendicitis [ 8 ].…”
Section: Main Textmentioning
confidence: 99%
“…Two studies reported the association of appendicitis and mesenteric lymphadenitis with SARS-CoV-2 infections. However, further ancillary studies on the resected specimen were recommended to confirm this hypothesis [ 8 ]. Similarly, a COVID-19 case has been identified in which a patient presented with a mild form of pancreatitis, absent of other causes [ 44 ].…”
Section: Main Textmentioning
confidence: 99%
See 1 more Smart Citation
“…Sanjay A Pai , 1 Bidisha Bhaduri, 2 Supraja Chandrasekar, 3 Phalguni Anand Alladi, 2 Tiffany Caza, 4 Anita Mahadevan, 5 T R Saiprasad, 6 Patrick Walker 4…”
Section: Correspondencementioning
confidence: 99%
“…5 There is a single report on the detection of SARS-CoV-2 RNA in the appendix. 6 The appendix showed granulomas, but there is no mention of the lymphoid follicles. Depletion of the lymphoid tissue in the lymph nodes, spleen, bone marrow and thymus is reported to be characteristic of infection with COVID-19.…”
mentioning
confidence: 99%